Hydrocarbon Generation Potential of Microbial Carbonate in the Western Qaidam Basin, China: Implication From Thermocompression Experiment - She, Min; Hu, Anping; Lv, Yuzhen; Chen, Wei; Liang, Jintong; Zheng, Lunju (Frontiers in Earth Science, 2022)
The potential of microbial carbonate rocks as hydrocarbon source rocks still remains uncertain. In order to evaluate the hydrocarbons generation and expulsion capability of microbial carbonate rocks, stromatolite from the western Qaidam Basin has been used for thermocompression experiment to simulate hydrocarbons generation and expulsion at temperature of 280 ºC to 380 ºC. The results show that the generation potential of total oil, residual oil, expelled oil and hydrocarbon gases for stromatolite are 143.39 mg/gTOC to 379.99 mg/gTOC, 47.08 mg/gTOC to 223.92 mg/gTOC, 71.12 mg/gTOC to 170.81 mg/gTOC, and 6.60 mg/gTOC to 101.74 mg/gTOC, respectively. The triple stages of hydrocarbons generation and expulsion evolution model has been constructed for stromatolite. The results show that the first stage is characterized by relatively slow oil generation, with associated hydrocarbon gases, having limited capability of oil expulsion in the temperature range of 320 ºC to 360 ºC (0.50%≤Ro≤0.70%). The second stage is characterized by rapid oil generation, with associated hydrocarbon gases, having incremental capability of oil expulsion in the temperature range of 320 ºC to 360 ºC (0.70%＜Ro≤1.15%). The third stage is characterized by hydrocarbon gas generation, with associated oil, having efficient oil expulsion capability in the temperature range of 360 ºC to 380 ºC (1.15%＜Ro≤1.45%). The experimental data of argillaceous dolostone, gray mudstone and marlstone, which were reported with the same hydrocarbon generation experimental method, was compared with the date of stromatolite. Compared with traditional source rocks, the oil generation potential of stromatolite is less than that of argillaceous dolostone and gray mudstone but above that of marlstone in the same amount of organic carbon. Especially, the hydrocarbon gas generation potential of stromatolite is about double that of traditional source rocks. Therefore, the experiment indicates that the microbial carbonate rocks in the western Qaidam Basin could be effective source rocks.